A spatial-temporal assessment of the Land Value Development Tax. (January 2016) - Garza, Nestor; Lizieri, Colin
Highlights: The neutrality of a Land Value Development Tax (LVDT) in the city of Bogota (Colombia) was assessed using spatial panel for the period 2000–2010. The case study offered excellent conditions to design a spatial and temporal policy assessment of static and dynamic neutrality. We found evidence that the LVDT was market neutral in a static sense because it diminished land prices. It was also neutral in a dynamic sense because it does not have building output effects. The LVDT assessment controlled land price feedback effects due to its spatial scattered application Abstract: We use information of the period 2000–2010 to assess the land market neutrality of a Land Value Development Tax (LVDT) in Bogota (Colombia). This city introduced the LVDT in 2004 and it offers an excellent vantage point for observation of its effects because of these reasons: (a) the LVDT follows a clear spatial and temporal application process; (b) the LVDT is applied over an extended metropolitan area regulated by a single master plan throughout all the years of application of the tax; (c) the city comprises a single public authority for revenue and taxation purposes; and (d) there has been no previous historical experience with the use of this type of land exaction in the city or its region. The LVDT is a one-time exaction levied where regulatory or infrastructural state interventions determine price increases, making it a difficult assessment subject when compared to the pure land tax. However, the aforementioned characteristics of our case study allow us to test its static (lowering of land prices) and dynamic (no development timing effects) neutrality in an emerging urban environment, using single and multi-equation spatial panel techniques.